SPECIFICS OF MODERN GREEK LANGUAGE TEACHING TO HISTORY STUDENTS - O. E. Petrunina (Moscow Polytechnic University, 2017)
The paper analyzes of the actual state of Modern Greek language teaching to history students. The article outlines the main difficulties faced by professors in teaching and students in mastering this rare language; describes the range of available textbooks and other teaching materials, notes their advantages and disadvantages; examines actual student books, workbooks and other teaching support materials for their relevance to perform the effective training of students of historical specialties; explores the possibilities of the Internet and its resources available today that contribute to the performance of the task.